Assessment of the water quality of Glacier-fed lake Neel Tal of Garhwal Himalaya, India. Issue 1 (2nd January 2019) - Kumar, Rahul; Sharma, Ramesh C.
ABSTRACT: Neel Tal is a glacier-fed lake, located at an altitude of 4, 382 m above m.s.l. in the Garhwal Himalaya, India. This lake is located at 30 Km from Gangotri, the world famous shrine of Hindus and 13 Km from the snout of Gangotri glacier known as "Gaumukh", that has been considered as the origin place of Holy River 'Ganga'. Assessment of surface water quality of a high altitude lake is important for providing drinking water to the trekkers, sages, and consumption by wildlife along with its conservation and management. Water Quality Index (WQI) method was applied to assess the water quality of Neel Tal, using 18 water quality parameters. The data for all the physical, chemical and biological parameters were collected in the months of June and August for a period of two years during 2014 and 2015 due to the accessibility of the lake as it remains under freezed condition for most of the time. The value of WQI was estimated to be 17.85 based on all the water quality parameters, which categorized the quality of water as 'excellent' during the study period. The coliform test also supported the findings of water quality of Neel Tal by WQI method.